2020
DOI: 10.1088/1367-2630/ab74a3
|View full text |Cite
|
Sign up to set email alerts
|

Separability of symmetric states and vandermonde decomposition

Abstract: Symmetry is one of the central mysteries of quantum mechanics and plays an essential role in multipartite entanglement. In this paper, we consider the separability problem of quantum states in the symmetric space. We establish the relation between the separability of multiqubit symmetric states and the decomposability of Hermitian positive semidefinite matrices. This relation allows us to exchange concepts and ideas between quantum entanglement and Vandermonde decomposition. As an application, we build a suite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…So the four vectors form a 4 × 4 singular matrix, which has rank at most three. However, by applying Matlab to matrix (34), we have shown that such a matrix does not exist. Hence, the product vector |u, v, w, y 8 A:D:E:BC does not exist.…”
Section: Four-partite Upbs From Five-qubit Upbsmentioning
confidence: 99%
See 1 more Smart Citation
“…So the four vectors form a 4 × 4 singular matrix, which has rank at most three. However, by applying Matlab to matrix (34), we have shown that such a matrix does not exist. Hence, the product vector |u, v, w, y 8 A:D:E:BC does not exist.…”
Section: Four-partite Upbs From Five-qubit Upbsmentioning
confidence: 99%
“…the PPT entangled states are related to the entanglement distillation problem [27,28], the detection of entanglement [29,30], as well as multipartite genuinely entangled states and entanglement-breaking subspaces [31,32]. The study of multipartite PPT states has also been devoted to the separability of completely symmetric states [33], the separability of symmetric states and vandermonde decomposition [34]. Hence, it is an important problem to construct novel PPT entangled states from UPBs, which may evidently motivated the study of fore-mentioned topics.…”
Section: Introductionmentioning
confidence: 99%
“…the PPT entangled states are related to the entanglement distillation problem [27,28], the detection of entanglement [29,30], as well as multipartite genuinely entangled states and entanglement-breaking subspaces [31,32]. The study of multipartite PPT states has also been devoted to the separability of completely symmetric states [33], the separability of symmetric states and vandermonde decomposition [34]. Hence, it is an important problem to construct novel PPT entangled states from UPBs, which may evidently motivate the study of the aforementioned topics.…”
Section: Introductionmentioning
confidence: 99%
“…where ρ i A and ρ i B are density matrices for the two subsystems A and B = Ā, with probabilities ∑ i p i = 1. Determining whether a mixed state is separable is NP hard [6][7][8] . The criterion for a state to have finite negativity, i.e.…”
mentioning
confidence: 99%